LHS = (2n)!
RHS = 2^n( n!)^2
for n=1,
(2n)! = (2)! = 1.2 = 2
2^n( n!)^2 = 2^1( 1!)^2 = 2
So LHS = RHS, condition is not satisfied.
for n = 2,
(2n)! = (4)! = 1.2.3.4 = 24
2^n( n!)^2 = 2^2( 2!)^2 = 16
So LHS > RHS
Your problem has errors!!!
I'll try to prove:
(2n)! >= 2^n( n!)^2 .. .... (ii)
for n = 1,
(2n)! = (2)! = 1.2 = 2
2^n( n!)^2 = 2^1( 1!)^2 = 2
So LHS = RHS, condition is satisfied.
let, for any arbitrary integer m, (ii) is satisfied.
So,
(2m)! >= 2^m(m!)^2
now, if n = m+1, (ii) becomes,
(2(m+1))! >=2^(m+1) ((m+1)!)^2
now,
(2(m+1))! = (2m+2))! = (2m+2)(2m+1) (2m)!
= 2(m+1)(2m+1) (2m)!
2^(m+1) ((m+1)!)^2 = 2.2^m (m+1)^2 (m!)^2
we have assumed, (2m)! >= 2^m(m!)^2
now, multiplying by 2(m+1)(2m+1) we get,
2(m+1)(2m+1) (2m)! >= 2^m 2(m+1)(2m+1) (m!)^2
now, 2^m 2(m+1)(2m+1) (m!)^2 = 2.2^m (m+1)(2m+1) (m!)^2
again 2m+1 > m+1
so, 2(m+1)(2m+1) (2m)! >= 2^m 2(m+1)(m+1) (m!)^2
or,
(2(m+1))! >=2^(m+1) ((m+1)!)^2
(ii) is true for n = m+1
(Proved)
2006-11-15 19:54:12
·
answer #1
·
answered by The Potter Boy 3
·
0⤊
0⤋
2!*n! < 2^n*n!*n!
2<2^n*n!
Proof it for n=1 and then n = n+1
you sure you aren't missing an equal sign in the inequality?
2006-11-16 03:54:56
·
answer #2
·
answered by ve1luv 2
·
0⤊
0⤋